STUDIES ON THE PRODUCTION OF SPORE CRYSTAL BY BACILLUS THURINGIENSIS CAMB 3-023 IN THE STIRRED FERMENTOR (Biological Sciences - PJSIR, 2003)
The insect pathogen Bacillus thuringiensis CAMB 3-023 was cultured using CSL-salt medium, in the stirred fermentor of 14 l capacity by batch process. The rates of aeration and agitation were kept at l/l/min and 200-300 rpm respectively. The sporulation hence in crystal protein synthesis was faster and much improved in comparison with shake flasks. It reached maximum (4.2x109/ml) in 48 h after inoculation with vegetative inoculum (10% v/v) developed in shake flasks. The bacterium was grown in the presence of different amounts of CSL (2.0-4.0% w/v). The optimum level of CSL was found to be 2.0% w/v. The addition of MnSO4 and CaCl2 during the course of fermentation enhanced sporulation.